Edge effects of the darkening of the light field in oblique incidence of a radiation flux on a medium; Journal of Soviet Laser Research; Vol. 5, № 1 - Kutlin A. P.; Larionov V. V. Vitaliy Vasilyevich; Mogil'nitskii S. B.; Savel'ev B. A. (1984, 1984)
В фонде НТБ ТПУ отсутствует